Hyperdimensional Neutral Monism: A Dimensional Approach to the Mind–Body Problem. - Frenkel, Jason (Philosophia, 2023)
This article introduces the concept of 'hyperdimensional neutral monism' as an elaboration and exploration of neutral monism. Neutral monism states that there is a single type of neutral, ontologically primary ultimate, which both the physical and the mental supervene on (Banks Philosophical Psychology, 23(2), 173-187, 2010). Hyperdimensional neutral monism (HNM) states that these ultimates exist in a more-than-4-dimensional realm and that the physical world of spacetime is a 4-dimensional aspect of this realm. Consciousness is the localized protrusion of spacetime into more than four dimensions. In order to explain these concepts, I utilize an aquatic metaphor of vortices appearing within a physical ocean. I compare HNM to panqualityism, which is another version of neutral monism (Coleman, Erkenntnis, 79(1), 19–44 2014 & Panpsychism: Contemporary Perspectives, ed. Godehard Bruntrup and Ludwig Jaskolla (Oxford: Oxford University Press, 2017), pp. 249–282 2016), and cosmopsychism (Shani Philosophical Papers, 44(3), 389-437, 2015, Shani & Keppler, 2018) which relies on a similar aquatic metaphor. I argue that HNM is a viable means of addressing the mind–body problem and the hard problem of consciousness (Chalmers, 1996, 2015, Panpsychism: Contemporary Perspectives,179(214), 2017, Chalmers, 2019).